Desmoplastic small round cell tumor 20 years after its discovery. (April 2015) - Mora, Jaume; Modak, Shakeel; Cheung, Nai-Kong; Meyers, Paul; de Alava, Enrique; Kushner, Brian; Magnan, Heather; Tirado, Oscar M; Laquaglia, Michael; Ladanyi, Marc; Rosai, Juan
ABSTRACT : Desmoplastic small round cell tumor (DSRCT) was proposed as a distinct disease entity by William L Gerald and Juan Rosai in 1991. Over 850 patients have been reported in the medical literature. A specific translocation, t(11;22)(p13;q12), is seen in almost all cases, juxtaposing the EWS gene to the WT1 tumor suppressor gene. DSRCT is composed of nests of small round cells with polyphenotypic differentiation, typically a mixture of epithelial, mesenchymal and neural features, surrounded by a prominent desmoplastic stroma. DSRCT has a predilection for adolescent and young adult males, and primarily involves the abdominal cavity and pelvis. Survival is low despite their initial response to multimodal treatment. Most patients relapse with disseminated disease that is unresponsive to further therapy.